Friction Modeling of Composite Brake Pads with Ulin Wood Powder (Eusideroxylon zwageri) - Putra, Muhammad Rezki Fitri; Isworo, Hajar; Yasin, Muhamad Noor; Subagyo, Rachmat (Universitas Negeri Malang, 2024)
This study investigates the performance of composite brake pads made of Ulin (Eusideroxylon zwageri) sawdust using simulation modeling, focusing on the pressure distribution, frictional stress, and contact state in five brake pad designs (DS0 to DS4). The brake pad designs used U-shaped grooves to improve cooling efficiency and debris removal. The results show that DS1 and DS2 exhibit the most uniform pressure distribution, with maximum values of 0.045 MPa and 0.048 MPa, respectively. DS1 recorded the highest peak frictional stress at 2.53 × 10-8 MPa, while DS2 showed consistent stress stability, reducing the possibility of uneven wear. DS3 achieved a balanced performance, with a maximum pressure of 0.062 MPa and a stable frictional stress distribution. In contrast, DS4 showed the highest stress (0.072 MPa) and increased “sliding” contact area, indicating reduced braking efficiency and potential for faster wear. Contact condition analysis showed predominantly “sticky” conditions on DS1, DS2, and DS3, which contributed to effective braking performance, while DS4 exhibited significant “sliding” conditions, which reduced friction efficiency. These findings confirm the potential of Ulin sawdust as an environmentally friendly brake lining material, with DS1 and DS2 emerging as the most suitable designs to achieve optimal braking performance and long life.